Some Ancient Monuments on the Iraqi-Persian Boundary - Edmonds, С. J.
Shaykhan relief; Naram-Sin relief of Darband-i Gawr; Bātās relief; Kēl-a Shīn stele; Tōpzāwa stele; pl. XLVIII: map of the qazā of Rawān-diz.